Opinions and attitudes of Italian healthcare workers towards recommended but not compulsory rotavirus vaccination - F. Amadori; E. Terracciano; I. Gennaio; V. Mita; D. Gargano; L. Zaratti; E. Franco; R. Arigliani (Taylor & Francis Group, 2021)
Rotaviruses (RVs) are a leading cause of viral gastroenteritis among children younger than 5. The incidence of RV disease can be reduced through the widespread use of vaccination, but coverage is low in many countries, including Italy. This fact reflects the poor consideration given to the RV vaccine, both by the population and by healthcare workers. Peoples' opinions are strictly dependent on the attitude of doctors and nurses. The aim of this work is the evaluation of healthcare workers' knowledge, attitudes and opinions regarding RV vaccination. The results of two surveys were compared; the first was carried out in 2017, soon after the Italian National Immunization Plan introduced the recommendation for the RV vaccine. The second was performed at the end of 2018, approximately 1 year after the adoption of a Law that introduced new compulsory vaccinations, not including the RV vaccine. In 2017, 182 questionnaires were collected, and 111 in 2018. An increase was observed in the percentage of participants who reported recommending the RV vaccine and a significant increase was found in the coverage the participants claimed to reach. Education of healthcare workers after the introduction of compulsory vaccination may prompt them to actively offer also recommended vaccines.